Gewissen und praktische Vernunft bei Immanuel Kant - Friedrich Ricken (Jesuit University Ignatianum in Krakow, 2017)
Conscience is a court of second instance. It is practical mind insofar as practical mind confronts us with the duty to judge our actions and insofar as practical mind examines whether we have fulfilled this second order duty. Conscience allows an action only if practical mind is certain that the action is not wrong, and it examines whether this claim has been fulfilled. Practical mind judges the action; conscience convicts and sentences, or acquits. Practical mind is not able to decide the quaestio facti whether I am responsible for the action; that is the task of conscience. The sanctions of conscience are moral feelings; it is only through moral feelings that we become aware of the necessity to judge our actions through practical mind.